Criminalized Masculinities: How Policing Shapes the Construction of Gender and Sexuality in Poor Black Communities. (29th May 2017) - Stuart, Forrest; Benezra, Ava
Abstract: With the intensification of policing and criminalization over the last three decades, residents of impoverished black communities are increasingly subject to street-level criminalization. This article examines how policing shapes the construction of gender and sexuality among its (potential) targets. Drawing on 12 months of fieldwork and interviews with 60 black youth living on Chicago's South Side, we find that in order to reduce the probability of a stop-and-frisk, young black men engage in reflexive and embodied masculinity performances. Aware that officers are most likely to detain and interrogate individuals who outwardly display toughness, emotional restrictiveness, and a proclivity for violence associated with the "cool pose" and the "code of the street, " youth attempt to communicate their innocence by exaggerating displays of emotional sensitivity, caring, vulnerability, and passivity. They concretely do so by overemphasizing (and even feigning) romantic involvement in heterosexual relationships—a strategy they refer to as "getting cover." Although "doing masculinity" in this manner may assist black youth in avoiding criminalization, it privileges dominant, mainstream (and often-unattainable) expressions of gender and sexuality while reinforcing hegemonic masculinity and heteronormativity. We offer a grounded, interactional framework for analyzing residents' situational and contingent responses to criminalization, which are characterized by a far greater degree of agency and innovation than previously assumed.